Ta'rib Strategies in Contemporary Arabic: An Analysis of Linguistic Adaptation and Its Socio-Cultural Implications - Rahmawati, Nita Putri; Maswani, Maswani; Farkhan, Muhammad (Arabi : Journal of Arabic Studies, 2025)
This study critically analyzes ta'rib (Arabization) strategies in contemporary Arabic, focusing on patterns of linguistic adaptation and their socio-cultural implications. Using a qualitative approach with an interpretive-constructivist paradigm, this study analyzes a documentary corpus that includes official publications of Arabic language institutions, academic literature, and a digital corpus of mass media. The results show that the ta'rib process involves systematic transformations at the phonological and morphological levels, with variations influenced by the domain of use and social context. Factors such as level of education, exposure to foreign languages, and attitude toward language modernization significantly affect the acceptance of ta'rib results. This research identifies the need for a holistic approach in developing ta'rib strategies that consider linguistic, socio-cultural, and technological aspects.